2011
DOI: 10.1103/physrevlett.106.224501
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Stretching as a Mechanism for Quantum Kinetic Energy Decay

Abstract: A pair of perturbed anti-parallel quantum vortices, simulated using the three-dimensional GrossPitaevskii equations, is shown to be unstable to vortex stretching. This results in kinetic energy K ∇ψ being converted into interaction energy EI and eventually local kinetic energy depletion that is similar to energy decay in a classical fluid, even though the governing equations are Hamiltonian and energy conserving. The intermediate stages include: the generation of vortex waves, their deepening, multiple reconne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 21 publications
(35 reference statements)
4
59
1
1
Order By: Relevance
“…Indeed, subsequent numerical simulations performed by both Kerr 11 and Kursa et al 12 have confirmed this scenario. With this in mind, it is plausible to think 9 that this mechanism may provide an alternative route for energy dissipation other than a Kelvin wave cascade [13][14][15] .…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Indeed, subsequent numerical simulations performed by both Kerr 11 and Kursa et al 12 have confirmed this scenario. With this in mind, it is plausible to think 9 that this mechanism may provide an alternative route for energy dissipation other than a Kelvin wave cascade [13][14][15] .…”
Section: Introductionmentioning
confidence: 56%
“…Indeed, using formulas (11) and (12) we can estimate the expected amount of energy to reach a boundary in a typical experimental apparatus for quantum turbulence. As the energy of a vortex ring is proportional to its radius then after n reconnections the vortex ring will contain a factor of (3/4) n of its original energy.…”
Section: Energy Transport or Energy Dissipation?mentioning
confidence: 99%
“…These figures can be compared with a similar stage (t = 1.25) in the evolution of anti-parallel quantum vortices in Kerr (2011) and to the cover illustration from Kerr (1996), which shows how the vortex lines twist as they extend from the anti-parallel interaction. What happens just after this configuration reconnects in Navier-Stokes calculations can be found in Kerr (2013).…”
Section: Three-dimensional Imagesmentioning
confidence: 99%
“…The resulting variation of the initial circulation in y-planes, Γ (y) is 1 %. (iii) The very long perturbed trajectory from Kerr (2011):…”
Section: Computational Method Domain and New Initial Conditionmentioning
confidence: 99%
See 1 more Smart Citation